POLICY ANALYSIS OF STUDY TOUR PROHIBITION ON ECONOMIC ASPECTS IN BOGOR CITY: Analisis Kebijakan Pelarangan Studi Tur Pada Aspek Ekonomi di Kota Bogor - Setiawan, Aditya Sugih; Ishak, Riani Prihatini; Rima Pratiwi Batubara (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of study tours as one of the pillars of the local tourism industry faces challenges, particularly in West Java, due to the instructions from the Governor of West Java. Meanwhile, the ban on study tours was also initiated by the high cost, which became a burden for some parents, especially those from middle and lower-income families. From an economic perspective, the ban on study tours also impacts the contribution of the local tourism sector. This research uses a qualitative and quantitative (mixed methods) approach. During the research and data collection phase, preliminary research, observations, and data gathering were conducted. Primary data was obtained from the results of distributing questionnaires to tourism business operators and in-depth interviews with key informants. Secondary data was obtained from literature studies. Meanwhile, data analysis refers to quantitative descriptive and Nvivo 12 data processing for qualitative data. The results show that the Development of Local Economies - local income is the most affected variable, with a 91% impact. This aligns with the ban and study tours, which have affected local income around tourist attractions.